The Potential of Hypofractionated Radiotherapy: A Revolutionary Treatment for Anorectal Malignant Melanomas - Thakur, Vandana; Vias, Poorva; Sharma, Hardik; Prashar, Pratibha; Jamwal, Aditya; Thakur, Anupam (Brazilian Journal of Oncology, 2025)
Mucosal melanomas generally arise from mucosal epithelium lining the respiratory, alimentary, and genitourinary tracts and usually carry worse prognosis than cutaneous melanomas. Anorectal melanomas account for 50% of gastrointestinal tract melanomas and 0.3 to 1% of all malignant melanomas. There are no specific treatment guidelines due to the scarcity of the disease, its unique biology, and challenges in management owing to the anatomic location. We report a case of anorectal malignant melanoma treated successfully with abdominoperineal resection followed by hypofractionated radiotherapy in a setting where financial toxicity limits treatment options. The patient presents complete response 2 years postdiagnosis, emphasizing that radiation therapy can be utilized for more than just palliation.
Keywords: malignant melanoma; hypofractionated radiotherapy; anorectal melanoma